Conversations with God Multilingualism among the Catholics in Belarus in the Late Twentieth and Early Twenty-First Centuries. Sociolinguistic study - Golachowska, Ewa (Sprach- und Kulturkontakte in Europas Mitte, 2020)
The book discusses the sociolinguistic status and prestige of the Polish language and the changes in the national identity of Catholics in Belarus due to the switch from Polish to Belarusian in the Catholic Church. The research shows that the national identification of Catholics in Belarus is changing. The oldest generations most often self-identify as Polish. For those from the middle and youngest generations, the link between nationality and their religion is not obvious as being a Catholic does not exclude a Belarusian self-identity. Belonging to the Catholic Church results from being baptized in the Catholic rite, while national identity can be defined in many ways and re-defined by various life experiences. Catholicism has proven to be a less debated and more durable category than nationality.